A Survey of Usage of Anytime Algorithm in Fault detection in Cloud Systems - Asadova, Farida; Varkonyi-Koczy, Annamaria R.; Kertesz, Gabor; Lovas, Robert (2023 IEEE 21st World Symposium on Applied Machine Intelligence and Informatics (SAMI), 2023)
Fault detection, which requires a lot of time and complexity, is one of the most difficult tasks for cloud computing. In this research, we investigate the utilization of the anytime algorithm in cloud-based fault detection techniques. Anytime algorithms are real-time decision-making algorithms that focus on time-deliberation. In this paper, the basic concepts of the Anytime algorithm in existing works as well as its benefits of usage are analyzed. Various literature is reviewed and combined for possible fault recognition and time deliberation. The paper includes details of anytime processing in fault detection in different subject areas. Based on the survey, we aim to define the algorithm processing implementation as future work.